Green Finance As A Tool To Support The Transition To A Sustainable Economy In Developing Countries - Halah Hashim Kadhim (International Journal on Economics, Finance and Sustainable Development, 2026)
Green finance is a financial service and product which is designed specifically to fund green projects and investments impacting positively on the environment including renewable energy projects, sustainable transportation, and efficient water and waste management, and green buildings. It is a qualitative change in the classic financial thought, as it incorporates the aspects of environmental concerns environmental and social considerations are included in the investment decision-making standards. The developing countries are most challenged, they bear the brunt of the climate changes even though they have the least contribution to the historical emissions and they have a huge funding gap estimated at over one trillion dollars per annum to implement the climate adaptation and mitigation projects and the actual flow of funding does not exceed with $100 billion per annum and international green finance is one of the strategic tools to close this gap and finance the shift of a sustainable economy balancing economic growth, social justice, and the preservation of the natural resources that will serve future generations. A complex web of international sources of green finance, multilateral sources, including IMF green Climate Fund, World Bank Group, regional development banks, including African and Asian Development Banks, specialized funds and bilateral financing by the developed countries is of great benefit to developing countries as it provides a way of great economic diversification, green employment, and transfer of clean technologies, but the difficulties of the developing countries lie in the fact that the structure is not well developed to fully utilize it, the most significant of which are weaknesses in the institutional and legislative frameworks, limited depth of domestic financial markets, technical capabilities, and high Thus, enabling the role of green finance will entail the incorporation of facilitating economic policies constructing the requisite regulatory frameworks, localization of the financial market, and empowering of the partnerships between governments and the business sector is needed to secure the intended transformation into more sustainable and sustainable economies amidst global climatic predicaments.